Competences, competences assessment, validity of instruments, Preschool Education - Rigoberto Marín Uribe; Isabel Guzmán Ibarra; Graciela Castro Aguirre (Universidad Autónoma de Baja California, 2012)
The purpose of this article is to describe the design process, validation and assurance of an instrument for the assessment of the success level of competences in preschool children. Initially is presented a theoretical and contextual framework of the competences in preschool. With this, it is problematized about the absence of tools for that the educators could perform the diagnostic evaluation of competences required in the reform of preschool education 2004. In the design of the instrument, the concept of "situation" is central. The validation and assurance included a process of pilotage with 512 preschool children with the implementing in practice of three different ways of application of the instrument. The results show high levels of assurance and power of discrimination that allow to distinguish significantly people by age and socioeconomic level, not finding differences by genre.